Knowledge shared : participatory evaluation in development cooperation - Jackson, Edward T., 1951-; Kassam, Yusuf, 1943- (Kumarian Press ; IDRC, 1998)
This book presents leading-edge analysis on the theory and practice of participatory evaluation around the world. With its instructive case studies from Bangladesh, El Salvador, Ghana, India, Indonesia, Kenya, Mexico, Nepal, and St Vincent, the book is a guide to a community-based approach to evaluation that is at once a learning process, a means of taking action, and a catalyst for empowerment. Knowledge Shared is the most comprehensive book now available on participatory evaluation. It is intended primarily as a tool for practitioners and policymakers in all segments of development cooperatio.